INOVASI MODEL PEMBELAJARAN MATEMATIKA ABAD 21: SEBUAH TINJAUAN LITERATUR - Zulfa, Lailatul; Umi Mahmudah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The 21st century brings new challenges and demands in education, especially in mathematics learning. Mathematical literacy now includes not only numeracy skills, but also critical thinking skills, problem solving, collaboration, and technological literacy. This article aims to examine various innovative learning models that have been applied in the context of 21st century mathematics education. Through a literature review of a number of national and international studies, it was found that approaches such as Problem Based Learning (PBL), Project Based Learning (PjBL), STEM education, Blended Learning, and the use of digital technology have a positive impact on improving students' learning outcomes and 21st century skills. This study recommends the development of an adaptive curriculum and ongoing teacher training so that these innovations can be implemented effectively.